Extraction of photovoltaic module model's parameters using an improved hybrid differential evolution/electromagnetism-like algorithm. (September 2015) - Muhsen, Dhiaa Halboot; Ghazali, Abu Bakar; Khatib, Tamer; Abed, Issa Ahmed
Highlights: Hybrid DE/EM algorithm is used to extract five parameters of PV module. Control parameters of hybrid algorithm are adjusted automatically. The proposed method offers better performance than other methods. Abstract: In this paper, an improved differential evolution with adaptive mutation per iteration algorithm (DEAM) is proposed for extracting PV module's model parameters. DEAM utilizes the attraction–repulsion concept which is used in the electromagnetism to boost the mutation operation of the original differential evolution (DE). Furthermore, a new formula to adjust the mutation scaling factor and crossover rate for each generation is proposed. The proposed method has been validated by experimental data and other previous methods. The results of the proposed method show a high agreement between the experimental and simulated I – V characteristics. The average root mean square error, mean bias error, coefficient of determination and CPU-execution time of the proposed method are 1.744%, 0.158%, 99.21% and 18.5975 s respectively. According to the results, the proposed method offers better performance than other methods in terms of accuracy, CPU-execution time and convergence.